The application of Augmented Reality (AR) technology to improve students' short story writing skills at SMA N 1 Jombang - Shofiani, Arisni Kholifatu Amalia; Nugraha, Alfian Setya; Sari, Raras Hafiidha; Hardinanto, Eko; Sulton, Agus; Faizi, Ahmad; Supratno, Haris (BAHASTRA, 2026)
This study aims to analyze the effectiveness of the application of Augmented Reality technology. Reality (AR) in improving the short story writing skills of high school students, who still face obstacles in developing ideas, narrative structure, and learning motivation. The study used a quasi-experimental design with a pre-test and post-test. control group This design involved 60 eleventh-grade students at SMA Negeri 1 Jombang. Data were collected through short story writing tests, motivational questionnaires, and interviews, and analyzed using paired- reference tests. sample t- test, independent t- test, and effect The results showed that the experimental group using AR experienced a significant increase compared to the control group, with an average score increase of 25.95% compared to 7.05%. Statistical tests showed a significant difference (p < 0.05) with an effect The size of the medium-high category. In addition, students' learning motivation in the experimental group was higher (8.5/10) than in the control group (6/10). These findings indicate that AR effectively improves the quality of short story writing in terms of ideas, narrative structure, and language style, as well as increasing student engagement in learning. This study contributes to the development of technology-based writing learning models by systematically integrating AR into the writing process. The limitations of the study lie in the limited duration of the intervention and the narrow sample scope. Future research is recommended to test the implementation of AR on a wider scale and over a longer period.